Usaha Meubel Jedong Sekarputih Balongpanggang Gresik - Radius Setiawan (Universitas Muhammadiyah Surabaya, 2017)
In this program partner SMEs are SMEs whose products are handicrafts Furniture in Jedong Sekarputih Balongpanggang Gresik.UKM involved partner there are 2, namely: UD. Future Furnituredan UD.Kharisma Meubel. The main problem is the difficulty in finding potential markets, partner SMEs do not have human resources specialized in marketing. Besides, the supply of raw materials from regions in East Java began to be small. This makes the problem because the price of raw materials becomes expensive because coupled with transportation costs. Approved issues for easing within 3 years: Marketing, management, production, product development, and human resources. The priority of solutions offered is on marketing issues, more specifically, will be optimized use of IT (internet) to advance the market. Strategies in 4P Mix (Product, Price, Promotion, and Place).